LA GESTIÓN DEL CAPITAL INTELECTUAL EN UNIVERSIDADES: UNA REVISIÓN DE LA LITERATURA - Carlos Mario Durango Yepes (Revista Ingeniería, Matemáticas y Ciencias de la Información)
The purpose of this paper is to review the existing research literature on intellectual capital (IC) in universities, toestablish a better understanding of how the world’s universities have responded to the challenge disclose your IC. Forwhich they were selected and assessed articles related to the topic, articulating according finds himself literature. Thepaper makes three specific contributions. The first contribution is to provide an overview of developments in theuniversities that have implemented methodologies and IC reports released so far this century. Second, information on ICmodels that have chosen universities as intangibles management system. The third is to provide methodologicalinformation to those most representative works of research on disclosure of IC.